MODULAÇÃO DA RESPOSTA IMUNE FRENTE À INDUÇÃO DE TOLERÂNCIA ORAL A TOXINA DERMONECRÓTICA PRESENTE NO VENENO DE Loxosceles intermedia e TOLERÂNCIA ORAL SOB A PERSPECTIVA DE SISTEMAS COMPLEXOS - Delgobo, Murilo (2014)
Brown-Spider’s venom (Loxosceles sp.) is presented as a complex mixture of toxins, able to induce skin necrosis with gravitational spreading, intense inflammatory response, edema induction and increase in vascular permeability in vivo. Recently, the biotechnological potential of the toxins was explored by its use in clinical test, in the study of inflammatory response, as a research tool in cell biology, as a biopesticide and in immunotherapy, through the production of antiserum. In this context, immunotherapy is broadly spread through the production of vaccines, available for the treatment of deleterious reactions developed in accidents. In the present work, we investigated if immunological tolerance induction to dermonecrotic recombinant toxin (LiRecDT1) and its mutated form (LiRecDT1 H12A), through its oral administration, could modulate inflammatory and deleterious responses triggered by dermonecrotic toxin. For this purpose, an oral tolerance protocol was designed, consisting in the administration of 10 μg of LiRecDT1 and LiRecDT1 H12A three times in a week, for three weeks. Adult Swiss mice were further immunized, and oral tolerance induction was observed by reduction in serum levels of IgG antibody anti-toxin when compared with control group. It was observed that mice tolerant to LiRecDT1 H12A present a reduction in paw edema, caused by the injection of 6 μg of dermonecrotic toxin in plantar surface hind paw. Mice tolerized with LiRecDT1 and challenged with 50 μg of dermonecrotic toxin, exhibited higher survival, when compared to control group. This effect was not observed in mice tolerized to LiRecDT1 H12A. The present findings suggested that oral tolerance induction to LiRecDT1 H12A was able to alleviate inflammatory responses triggered by dermonecrotic toxin in paw edema and oral tolerance to LiRecDT1 increase survivability in challenge. The results shown that LiRecDT1 and LiRecDT1 H12A can be explored as a tool in the induction and study of oral tolerance phenomena. The generation of T regulatory cells (Tregs) and following involvement of immunosuppressive cytokines might take part in the modulation of immune response.